The effect of freshwater pulse on Aurelia aurita (Linnaeus 1758) (Cnidaria: Scyphozoa): an ecohydrological solution for controlling jellyfish blooms - Amorim, Katherine (2016)
Dissertação de mestrado, Ecohidrologia, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015